2021
DOI: 10.1155/2021/8882594
|View full text |Cite
|
Sign up to set email alerts
|

Total Polyphenol and Flavonoid Content and Antioxidant Capacity of Some Varieties of Persea americana Peels Consumed in Cameroon

Abstract: Fruit peels are increasingly being used as functional foods nowadays. Peelings of twelve varieties of Persea americana fruits consumed in Cameroon were investigated for their phenolic compounds (polyphenols and flavonoids) using three solvents systems, water, ethanol: water (50 : 50 v / v ), and ethanol, and antioxidant activity using total antioxidant capacity (TAC), ferric re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 48 publications
(58 reference statements)
1
8
0
Order By: Relevance
“…The values obtained for the flavonoid contents in PAE and CAE were 15.5 ± 0.35 and 5.75 ± 0.35 mg rutin/g of dry extract, respectively. The fact that flavonoid components were more abundant in the ethanolic extracts agree with the findings of Dibacto et al (2021) where ethanol extract gave the highest flavonoid content among three solvents: ethanol, ethanol: water; 1:1 v/v and water.…”
Section: Resultssupporting
confidence: 91%
“…The values obtained for the flavonoid contents in PAE and CAE were 15.5 ± 0.35 and 5.75 ± 0.35 mg rutin/g of dry extract, respectively. The fact that flavonoid components were more abundant in the ethanolic extracts agree with the findings of Dibacto et al (2021) where ethanol extract gave the highest flavonoid content among three solvents: ethanol, ethanol: water; 1:1 v/v and water.…”
Section: Resultssupporting
confidence: 91%
“…This last study also reported TPC values for the seed, from 16.99 to 60.82 mg GAE/g DE, close to resulting values from this assay. On the other hand, higher TPC from ‘Hass’ hydroethanolic extract was reported by Dibacto et al (813 ± 12 mg GAE/g DM) [ 51 ]. Differences among values are due to many factors, such as type of extractant, extraction method, fruit size, ripening stage, etc.…”
Section: Resultsmentioning
confidence: 86%
“…These values are much lower than those obtained in this work. On the other hand, Dibacto et al [ 33 ] reported TAC values for avocado peel extracts of 129.47 mg AAE/g DAP using water as solvent, 132.87 mg AAE/g DAP with 50% ethanol, and 130.02 mg AAE/g DAP for pure ethanol. These results are more like those obtained in the current investigation.…”
Section: Resultsmentioning
confidence: 99%